IDENTIFICATION OF PROFILES OF STREET CHILDREN AND MITIGATION INTERVENTION PLANS - Herawati, Netty; Rohmah, Nailur (MOTIVA: JURNAL PSIKOLOGI, 2024)
Abstract: The treatment of street children so far is uncompromising and less serious, ignoring their rights and freedoms as citizens to be protected by the state. Therefore, the aim of this study is to create mitigation and intervention plans on street children. The approach in this study used surveys with cluster sampling techniques because they were limited to areas in Bangkalan district. The sample group consisted of girls and boys, aged 8 to 18, who worked on the street for at least a month before the survey. There's a total of 43 respondents. The results showed that based on the age of respondents, 8-10 years was 16.3%, 12-15 years was 23.3% and 16-18 years was 60.5%. Based on the level of education, respondents did not pass SD was 18.6%; passed SD 23.2%, not passed SMP 37.2% and passed SMP 20.9%. According to street activities carried out: begging 13.9%, playing music 30.2%, cleaning car glass 11.6%, street clowns 9.3% and trade 34.9%, according to the results, then mitigation measures can be taken by increasing public care, not giving in the street when begging but can be through social foundations or official government institutions such as social services. Internal intervention planning can be done by providing work skills training, financial management training and psycho-education for psychological formation. Externally, governments can help in economic and social empowerment. Governments can facilitate through localization of trade activities in conducting business, providing capital assistance with loan savings system. In conclusion, it is necessary to work comprehensively with governments, communities and social institutions to care for each other to improve the well-being of street children in various aspects, both economic, social and psychology.Keywords:  street children, mitigation, intervention plan